Description of the scientific-disciplinary reader profile of Spanish-speaking audiology professionals - Cañete, Oscar M.; Hernández Ricoy, Paula (Auditio, 2022)
Audiologists are recognized in Spain and most countries in Latin America and have practised in various fields for more than 40 years. Despite this, a paucity of information exists regarding audiologists’ engagement with scientific journals both as readers and authors alike. The aim of this paper was to describe the scientific-disciplinary reader profile of Spanish-speaking audiology professionals. A questionnaire was distributed online with 16 questions grouped into two sections: 1) General and demographic data and 2) Readership profile. A total of 200 questionnaires were completed. With the results, a qualitative analysis was performed and a summary was written for each question. General audiology and hearing aids/amplification systems were found to be the areas of greatest interest among respondents (74% and 71%, respectively). In the readership profile section, 66% of respondents reported consulting scientific journals (at least once a month). The most common reason, given by 51% in this group, was to keep up to date. However, 81% of respondents reported never having published in a peer-reviewed journal. The main reason for not publishing was lack of confidence to write an article (51%). Despite audiologists showing a keen interest in reading audiology journals, only a small proportion submits articles for publication.